Hybrid molecules of carvacrol and benzoyl urea/thiourea with potential applications in agriculture and medicine - Pete, Umesh D.; Zade, Chetan M.; Bhosale, Jitendra D.; Tupe, Santosh G.; Chaudhary, Preeti M.; Dikundwar, Amol G.; Bendre, Ratnamala S. (Bioorganic & Medicinal Chemistry Letters, 2012)
Benzoyl phenyl urea, a class of insect growth regulator's acts by inhibiting chitin synthesis. Carvacrol, a naturally occurring monoterpenoid is an effective antifungal agent. We have structurally modified carvacrol (2-methyl-5-[1-methylethyl] phenol) by introducing benzoylphenyl urea linkage. Two series of benzoylcarvacryl thiourea (BCTU, 4a-f) and benzoylcarvacryl urea (BCU, 5a-f) derivatives were prepared and characterized by elemental analysis, IR, H-1 and C-13 NMR and Mass spectroscopy. Derivatives 4b, 4d, 4e, 4f and 5d, 5f showed comparable insecticidal activity with the standard BPU lufenuron against Dysdercus koenigii. BCTU derivatives 4c, 4e and BCU 5c showed good antifungal activity against phytopathogenic fungi viz. Magnaporthe grisae, Fusarium oxysporum, Dreschlera oryzae; food spoilage yeasts viz. Debaromyces hansenii, Pichia membranifaciens; and human pathogens viz. Candida albicans and Cryptococcus neoformans. Compounds 5d, 5e and 5f showed potent activity against human pathogens. Moderate and selective activity was observed for other compounds. All the synthesized compounds were non-haemolytic. These compounds have potential application in agriculture and medicine. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Antifungal agents; Benzoyl carvacryl urea; Benzoyl phenyl urea; Crop protection agents; Insect growth regulators